Pengaruh Komunikasi dalam Keluarga terhadap Motivasi Belajar Mahasiswa Komunikasi dan Penyiaran Islam Universitas Ibn Khaldun Bogor - Oktavioni, Venda; Hasan Basri Tanjung; Indry Nirma Yunizul Pesha (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Communication in the family is important to create good relationships between family members. Lack of communication and parental attention can affect the learning motivation of 4th and 6th semester students of the Islamic Communication and Broadcasting study program, Ibn Khaldun University, Bogor. This study uses a quantitative method with a descriptive approach. The data collection technique uses a questionnaire distributed to 67 student respondent. The data analysis technique uses a simple linear regression test and the (t) test. The results of study showed that communication in the family has an influence of 59,4% on the learning motivation of 4th  and 6th semester students of the Islamic Communication and broadcasting study program, Ibn Khaldun University, Bogor. In addition, see from the Beta Standard Coefficient value of 0,771, it means that communication in the family has a positive influence on student learning motivation.